Insight into roles of different types of additives on mechanical and crystalline properties of polylactic acid. Issue 11 (20th October 2021) - Zhang, Ligang; Tian, Hongchi; Chen, Jun; Hao, Yanping; Liu, Yang; Sun, Yawei; Duan, Hongyun
Abstract: With people's awareness of environmental protection, the requirement of eco‐quality is increasingly demanding, particularly a more profound reflection in the field of materials. Polylactic acid (PLA) is a hopeful biodegradable thermoplastic material while its adverse nature restricts the practical applications. In this work, a one‐step reactive extrusion method was adopted to improve some properties of PLA by melt blending with some active additives, including commercial epoxy‐based chain extender, that is, ADR4468 of BASF, Germany; thermoplastic polyurethane thermoplastic polyurethane (TPU) elastomer, that is, DN‐5380 of Dawn, China, and mineral nucleating agent talc, that is, AH250CL of Aihai, China. Their influences on mechanical properties and crystallization behaviors of PLA were explored, and the detailed mechanisms were also discussed. It is found that ADR chain extender played a key role in improving the strength and rigidity of the composites, and methylenediphenyl diisocyanate type TPU elastomer could significantly enhance the toughness and ductility of PLA materials, while talc had a positive impact on regulating the cooling crystallization behavior of PLA. In particular, only trace ADR4468 (0.4 wt%) could effectively enhance its tensile and flexural strengths of neat PLA by 6.3% and 13.4%, respectively. Reactive polyurethane with 5 wt% significantly improved its elongation at break by 36.5%. The micro‐sized talc‐nucleating agent enhanced the cooling crystallization degrees to 24.7% from 4.8% for PLA blended with trace chain extender. The analysis results indicated that the functional group reactions between the active additives and PLA played key roles in improving the related properties. The output has certain reference values for PLA modification strategy, and will pave a route for endowing PLA materials with specific and required nature. Abstract :